Alice and DIVER: A software architecture for building virtual environments - Pausch, Randy; Conway, Matthew; DeLIne, Robert; Gossweiler, Rich; Miale, Steve (CHI '93 INTERACT '93 and CHI '93 Conference Companion on Human Factors in Computing Systems, 1993)
We are developing a rapid prototyping system built on an object-oriented, interpreted language which allows small interdisciplinary teams to quickly create and modify three-dimensional interactive simulations. Like other systems, we separate the simulation and presentation frame rates, but unlike existing systems, we do so in such a way that the application-level programmer need not understand the multi-process architecture. The system has been used for building perceptual psychology experiments, for replicating techniques developed by other researchers, and for experimenting with novel three-dimensional interaction techniques.